Implementing “Escape Room” to Enhance Students' Reading Comprehension of Narrative Texts: A Classroom Action Research - Atmadja, Dhimas Dwyki; Fauzi, Dicky Hilman; Izlin, Rosita; Faridah, Didih; Purwaningsih, Juki (English Lecturers and Teachers Association (ELTA), 2025)
Reading comprehension, particularly of narrative texts, remains a persistent challenge among Indonesian high school students. Conventional reading instruction often results in passive learning and low student engagement. This study aimed to investigate the effectiveness of the “Escape Room Reading Challenge” as an innovative, gamified instructional strategy to enhance students’ reading comprehension and engagement. This Classroom Action Research (CAR) was conducted in two cycles involving 33 tenth-grade students at SMAN 1 Baregbeg, Ciamis, Indonesia. The research followed the Kemmis and McTaggart model, which consists of planning, acting, observing, and reflecting stages. Data were collected through reading comprehension tests, observation checklists, and field notes. The results indicated a consistent improvement in students’ reading comprehension and classroom participation. In Cycle 1, the average post-test score increased from 61.58 to 69.09. Following instructional refinement in Cycle 2, the average post-test score rose significantly to 83.76. Observation data revealed that active participation also improved from 60% in Cycle 1 to 90% in Cycle 2. These findings suggest that the escape room approach effectively promotes critical thinking, teamwork, and student motivation while supporting deeper comprehension of narrative texts. The study concludes that integrating gamified strategies like escape rooms into reading instruction can create a more meaningful, collaborative, and enjoyable learning environment. Further research is recommended to explore its adaptability across genres and its long-term impact on literacy development.